2001
DOI: 10.1111/j.1937-8327.2001.tb00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping in the Instructional Design Process

Abstract: Instructional models guide designer activity as they attempt to solve instructional problems. Models provide structure to the project, problem solving strategies, evaluation, and feedback. This paper is designed to examine Rapid Prototyping, a model born in the computer age. Rapid Prototyping embraces computer design strategies, constructivist learning theory, and cognitive psychology. This paper will first look at the “classic” forms of instructional design models, which form the foundation of instructional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…It refers to a “process [which] involves quickly developing a prototype product in the very early stages of an instructional design project and then going through a series of rapid tryout and revision cycles until an acceptable version of the product is produced” (Reiser, 2001, p. 63). Prior research (e.g., Brown & Green, 2015; Desrosier, 2011; Nixon & Lee, 2001) suggests that when compared with traditional ID models, rapid prototyping exhibits the following four advantages:…”
Section: Literature Reviewmentioning
confidence: 99%
“…It refers to a “process [which] involves quickly developing a prototype product in the very early stages of an instructional design project and then going through a series of rapid tryout and revision cycles until an acceptable version of the product is produced” (Reiser, 2001, p. 63). Prior research (e.g., Brown & Green, 2015; Desrosier, 2011; Nixon & Lee, 2001) suggests that when compared with traditional ID models, rapid prototyping exhibits the following four advantages:…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Characterized by heavy front-end analysis -analysis of learners, context, needs, objectives, etc • Instructional assessments and activities are designed and developed • Deliverable product delivered to stakeholders at end of the process • Evaluation of product by end users provide feedback for improvements needed • Steps in approach can be linear or iterative, but iterations usually involve the phases after deliverable launches and feedback on usage is received Rapid prototyping, a time-compression technique, aims to complete the instructional design process in less time while using fewer resources in comparison to traditional ID approaches. Nixon and Lee (2001) found that "rapid prototyping opens up the boundaries found in traditional models (2008, p. 102). Jones and Richey (2000) expanded by stating "RP involves the development of a working model of an instructional product that is used early in a project to assist in the analysis, design, development and evaluation of an instructional innovation.…”
Section: Rapid Prototyping Compared To Classic Instructional Design Mmentioning
confidence: 99%
“…One solution to this dilemma is the use of rapid prototyping methodologies" (p. 63). Nixon and Lee (2001) summarize the importance of selecting an appropriate instructional design model as they "provide structure to the project, problem solving strategies, evaluation and feedback" (2008, p. 95).…”
Section: Rapid Prototyping Compared To Classic Instructional Design Mmentioning
confidence: 99%
“…A prototype is an early and incomplete example of the final program (Bssmer & Wedman, 1995). The use of prototypes in training design and development has increased considerably over the last decade in part because they can expedite time to implementation (Nixon & Lee, 2001;Tripp & Bichelmeyer, 1990). For the purposes of formative evaluation, a prototype should include some portion of the training materials presented in the format intended for the final program.…”
Section: Prototypementioning
confidence: 99%